China’s softpower in Peru - Aquino Rodríguez, Carlos (2017)
China as an emerging power seeks to promote its culture, language, view of the world, that is, its soft power. In the case of Peru, a country with a significant presence of Chinese immigrants, a long history of relations, and increasing important in trade, through the establishment of Confucius Institute and other actions China try to reinforce its traditional good image that has in Peru. This article analyze the Chinese efforts to increase its soft power in Peru. Keywords: China’s Soft power, Confucius Institute, Peru China trade relationship, Chinese immigration to Peru.